PSYCHOLOGICAL ASPECTS OF DEVELOPMENT OF MANAGEMENT COMPETENCE IN STUDENTS OF HIGHER EDUCATION INSTITUTIONS - Yakubov Umid Bobayevich (International Scientific and Current Research Conferences, 2024)
The management problem has become one of the most urgent problems of the late 20th and early 21st centuries. This situation is explained by the increased role of the human factor in all social processes. In addition, personal qualities, such as a passion for leadership and a tendency to strive for success in service positions, began to appear in people from an early age. Such socio-psychological phenomena made it urgent to increase the effective role of this factor in matters such as, first of all, further improvement of the management sphere, increase of its effectiveness, labor productivity and improvement of human relations.